The trajectory of a drop: An experience report with students of Differential and Integral Calculus - Almeida, Moisés Ceni de; Barbosa, Renata Cardoso; Musmanno, Leonardo Maricato; Souza, Natália Pedroza de (Educação Matemática Debate, 2023)
The article presents an experience report of a formative activity carried out by students of Differential and Integral Calculus of the Mechanical Engineering course of a public institution in Rio de Janeiro. Among the motivators are the failure rates in the discipline and the theoretical foundation was experimentation. Given a previously structured guide, students analyzed the trajectory against time of a drop of water in an oil bottle, producing hypotheses about displacement, using a double-entry table. The mobilized contents were affine function, derivatives and least squares method. To verify hypotheses, students used geometry software and spreadsheets. It was observed that Experimentation promoted critical thinking, making students managers of their own knowledge.